Implementing a healthy lifestyle program in residential out‐of‐home care: What matters, what works and what translates?. (8th March 2022) - Green, Rachael; Hatzikiriakidis, Kostas; Tate, Ruby; Bruce, Lauren; Smales, Madelaine; Crawford‐Parker, Anna; Carmody, Sarah; Skouteris, Helen
Abstract: The Healthy Eating, Active Living Matters (HEALing Matters) program is being scaled up across residential out‐of‐home care (OOHC) in Victoria, Australia and is providing young people with the knowledge, skills and resources to promote better health through healthy eating and activity. HEALing Matters was piloted as the HEAL program, a dual‐intervention program that aimed to provide young people living in residential care with education and opportunities to improve their eating and physical activity habits, while simultaneously building the capacity of their carers to promote, encourage and role model healthy lifestyle behaviours. Qualitative findings indicated that HEAL resulted in increased participation in community sport, increased availability of sports equipment, healthy meal preparation and healthy food availability and improvements in perceived young person self‐esteem and independent living skills. Findings also revealed some limitations of the program. Following the pilot, a participatory methodological approach was used to better understand how to align the HEAL program with individual and community needs. This approach engaged diverse stakeholders to better understand the barriers and enablers, address limitations, identify key intervention points and build trust and a shared vision to co‐design the HEALing Matters program. HEALing Matters is now delivered within a framework that is informed by attachment, trauma and resilience theories. This paper outlines the HEALing Matters journey from what matters, to what works, to what translates in relation to a healthy eating and active living intervention in OOHC.